1989
DOI: 10.1017/s0033291700011053
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of structural brain changes in schizophrenia: age of onset as a predictor of cognitive and clinical impairments and their cerebral correlates

Abstract: SYNOPSIS A range of cerebral structures was assessed in a series of 172 CT scans of groups of psychiatric patients (including 101 in-patients with chronic schizophrenia) and related to assessments of clinical state and psychological function. Ventricular indices were increased in patients with schizophrenia by comparison with patients with other psychiatric disorders: brain area, which is modestly positively correlated with ventricular indices, was significantly (P < 001) reduced in patients with schizophrenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(69 citation statements)
references
References 55 publications
1
68
0
Order By: Relevance
“…19,20 Häfner et al 1989 21 found that, specifically for men, symptom severity decreased with later onset. In males: (a) vs (c) testing non-parametrically using Mann-Whitney Rank-sum Test (P = 0.019) and testing parametrically using Students t-test (P = 0.022, ⌬ mean age = 4.7 years, 95% CI: 0.7-8.8 years); and (c) vs (a + b) (corresponding to genotypes containing the 1-bp deletion vs those that do not), Mann-Whitney Rank-sum Test (P = 0.034), Students t-test (P = 0.043).…”
Section: Figurementioning
confidence: 99%
“…19,20 Häfner et al 1989 21 found that, specifically for men, symptom severity decreased with later onset. In males: (a) vs (c) testing non-parametrically using Mann-Whitney Rank-sum Test (P = 0.019) and testing parametrically using Students t-test (P = 0.022, ⌬ mean age = 4.7 years, 95% CI: 0.7-8.8 years); and (c) vs (a + b) (corresponding to genotypes containing the 1-bp deletion vs those that do not), Mann-Whitney Rank-sum Test (P = 0.034), Students t-test (P = 0.043).…”
Section: Figurementioning
confidence: 99%
“…(ii) Cortical mass (Zipursky et al, 1992;Ron et al, 1992) or brain size (Brown et al, 1986;Johnstone et al, 1989;Pakkenberg, 1987;Pearlson et al, 1989) is decreased.…”
Section: Homogeneity Of Structural Brain Changesmentioning
confidence: 99%
“…When other factors are taken into account, those with an onset of psychosis younger than the mean are more likely to have negative symptoms and evidence of cognitive impairment [7], They are also more likely to show temporal disori entation, impairments on the Boston naming test and in the Peabody test of premorbid intellectual function. These patients are ap parently on a trajectory of dysfunction that links premorbid deficits with poor outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Ovchinni kov, Snezhnevsky, Carpenter and Wing -see 6] had adopted between positive and negative symptoms could be discerned. Positive symp toms it seemed were more likely, and negative symptoms (at least when restrictively defined) less likely to respond to neuroleptic medica tion [7], Negative symptoms were more likely to be accompanied by cognitive impairments. If one accepted that there were two compo nents to the disease process a simple separa tion of the major features of the disease was possible: These syndromes were not indepen- …”
mentioning
confidence: 98%